Application of Individual Nursing Care Software for Public Health Nurses at the Indramayu District Health Center - Nengsih Yulianingsih; Priyanto Priyanto; Kayubi Kayubi (Universitas Pendidikan Indonesia, 2022)
Public Health Nursing (Perkesmas) is one of the health centers' efforts that supports the improvement of public health status by integrating nursing knowledge/practice with public health through the support of active community participation. Perkesmas service activities can be carried out inside and outside the Puskesmas building. Nurses provide nursing care for individuals who come to the puskesmas, provide family nursing care and nursing care for special groups/health-prone groups in the Perkesmas target area (home visits to vulnerable families). The problem for partners who are appointed in this community service program is the Documentation of Individual Nursing Care in the Perkesmas program which is less than optimal. This program offers solutions that are expected to help solve partner problems. The method used is to develop an application system in the documentation of individual nursing care in the health care program. As a result of this community service program, partners have an application system that will make it easier for community health workers in documenting individual nursing care in the community health program. The results of this program will also be published in accredited national or international journals.